The interconnection in regulation of jurisdiction in the proposal for a European Regulation in matters of parenthood with the Brussels III ter and III Regulations - Guzmán Peces, Montserrat (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The purpose of this work is to analyze the competence criteria in the Proposal for a European Regulation on parenthood and its relationship with other European Regulations, such as Regulation (EU) 1111/2019, especially in the field of parental responsibility and protection of children and Regulation (EU) 4/2009 on maintenance obligations. In addition, the possibility of accumulation of actions is analyzed both in national jurisprudence and in community jurisprudence as a key element to achieve the priority objective of reducing procedural costs both for families and for the judicial systems of the Member States.